Blast pressure leakage into buildings and effects on humans. (2017) - Malhotra, Ashok; Carson, Dan; McFadden, Scott
Abstract: In the event of a bomb blast taking place outside a building at the ground level, a hemispherical pressure wave travels in all directions and impacts the buildings and other structures in its path. The exterior walls, windows, doors and the structural system are impacted. The pressure wave enters the building through broken glass at doors and windows, blast damaged exterior cladding and any other openings in the exterior of the building. The increase in ambient pressure experienced inside the building depends upon the area of openings in the exterior walls and the roof, the air pressure due to the blast at the exterior wall and roof surface, the duration of the blast and the volume of the interior space. Depending upon these factors, the interior pressure can increase above the threshold of human tolerance, thereby causing injuries to the occupants in the form of damage to lungs and eardrums, in addition to injuries caused by broken glass and other damaged building components. This paper will present a simple method of estimating pressure buildup near the exterior walls and other locations subject to leakage of blast pressure from the outside. The threshold of human tolerance to high air pressure will also be indicated.